DETERMINANTS OF ACCESSING PORNOGRAPHY CONTENT BEHAVIOR AMONG HALU OLEO UNIVERSITY STUDENTS: A CASE STUDY - Handayani, Listy; Nurfadilah H, Siti; Putri, Anggi Faradiba; Sanggo, Raqhil Caesario; Alghi, Anugrah Febrian (Universitas Halu Oleo, 2024)
ABSTRACT The increasing of online communication media presence makes it easier to share and access pornographic content in Indonesia. Ministry of Communication and Information reported that in 2023, there were 171 million internet users with 1,028,702 of them have accessed pornographic contents. There is no data regarding the amount of pornographic content accessed in Kendari City, however the initial observation information there are several Halu Ole University (UHO) students who have access pornographic content habit. This study aimed to overview of the determinants of pornographic contents access behavior among students at UHO. A qualitative study with case study design was conducted in this study. The data collected through in-depth interview to 4 informants who chosen by purposive sampling technique. This study result found that the students who have accessing pornographic contents were over 20 years old and all of them have good knowledge related to the pornographic contents and its impacts. They did not receive supervision or warnings from their parents regarding the prohibition on accessing pornographic contents. This behavior also influenced by how simple it is to access pornographic content on social media (such as Twitter, Facebook, and Instagram). Therefore, students must be observant and wise in accessing internet content, parents must be strict to supervise and guide their children about what content can be accessed and it is hoped that the Communication and Information Ministry will ban the pornographic content. Keywords: Accessing, Content, Determinants, Pornographic